Financial Spillovers to Chile - Podpiera, Jiri (IMF Working Papers; Working Paper ;, 2012)
This paper quantifies financial spillovers from global risk factors to banks' funding costs in Chile. It decomposes Chilean banks' bond and interbank spreads into domestic and external factors. The results suggest moderate spillovers. On average, global spillovers pushed up bank bond and interbank spreads in Chile by about 50 basis points in 2008-12. While in 2008-09, most spillovers originated in the U.S., in mid-2010 onwards, European distress played a prominent role.